Influence of Solution Annealing Temperature on Crystallographic Texture and Grain Disorientation of Nb-Enhanced Maraging Steel: An EBSD Analysis - Mohammad Masoumi; Gerardo Pérez; Guilherme Schmalz; Antonia I.M. Silva; Pedro L.M. Torquato; Luis FG Herculano; Isabel Barros; Miloslav Béreš; Hamilton F.G. de Abreu (Materials Research)
This study investigates the microstructural and crystallographic changes in a novel Nb-enhanced, Ti-reduced maraging steel. The hot-rolled steel was solution annealed at two different temperatures followed by aging. The Electron Backscatter Diffraction (EBSD) analysis of hot-rolled sample revealed a predominant {112}//RP texture, reoriented to {110}//RP during aging to minimize internal energy and stress. Solution annealing at 820oC followed by aging favored a {111} orientation, resulting in minimal crystallographic defects and grain distortion. In contrast, higher solution annealing temperatures promoted the formation of {001} cleavage planes, increasing brittleness and crystal defects, thereby impacting the material's suitability for high-performance applications.